Li insertion into Li4Ti5O12 spinel prepared by low temperature solid state route: Charge capability vs surface area. (1st March 2018) - Zukalová, Markéta; Fabián, Martin; Klusáčková, Monika; Klementová, Mariana; Pitňa Lásková, Barbora; Danková, Zuzana; Senna, Mamoru; Kavan, Ladislav
Abstract: Li4 Ti5 O12 spinel powders with different surface areas are prepared by a novel low temperature solid state route with subsequent mechanical disintegration. X-ray diffraction analysis proves the presence of majority of Li4 Ti5 O12 phase with small amount of rutile and WC impurities. Transmission electron microscopy analysis evidences the presence of two morphologies, larger Li4 Ti5 O12 crystals surrounded by nanocrystals of Li4 Ti5 O12. This finding is supported by cyclic voltammetry of Li insertion and electrochemical impedance spectroscopy. The concentration ratio of these two morphologies in particular sample depends on its post ball milling time. Cyclic voltammetry of Li insertion and galvanostatic chronopotentiometry at 1C rate confirm the highest charge capacity for Li4 Ti5 O12 spinel with surface area of 21 m 2 g −1 . Due to optimized ratio of two particular morphologies this material (coded LTO_21) without any carbonaceous additive possesses excellent long time cycling stability during galvanostatic chronopotentiometry at 1, 2 and 5C. Its discharge capacities reach 170 mAh g −1 at 1C, 167 mAh g −1 at 2C and 160 mAh g −1 at 5C rates with 100% coulombic efficiency. The capacity drop was less than 1% for charging rates of 1 and 2C and about 5% at 5C. The discharge capacity of all the reported samples significantly outperforms that of commercial lithium titanate (Aldrich) with surface area of 12.5 m 2 g −1 exhibiting discharge capacities of 95 mAh g −1 (cyclic voltammetry) and 77 mAh g −1 or 35 mAh g −1 in galvanostatic chronopotentiometry at 1 or 2C rates, respectively. Hence, our novel low temperature solid state route with subsequent mechanical disintegration represents energy saving pathway towards promising anode materials for fast and stable Li-ion batteries. Graphical abstract: Image 1 Highlights: New low temperature solid state route provided Li4 Ti5 O12 with different surface area. Discharge capacity of LTO reaches 170, 167 and 160 mAh g −1 at 1, 2 and 5C, resp. The capacity drop was less than 1% after 50 cycles at 1 and 2C rate.